The miRNA transcriptome of cerebrospinal fluid in preterm infants reveals the signaling pathways that promote reactive gliosis following cerebral hemorrhage - Gialeli, Andriana; Spaull, Robert; Plösch, Torsten; Uney, James; Llana, Oscar Cordero; Heep, Axel (Frontiers in Molecular Neuroscience, 2023)
Germinal Matrix-Intraventricular Haemorrhage (GM-IVH) is one of the most common neurological complications in preterm infants, which can lead to accumulation of cerebrospinal fluid (CSF) and is a major cause of severe neurodevelopmental impairment in preterm infants. However, the pathophysiological mechanisms triggered by GM-IVH are poorly understood. Analysing the CSF that accumulates following IVH may allow the molecular signalling and intracellular communication that contributes to pathogenesis to be elucidated. Growing evidence suggests that miRs, due to their key role in gene expression, have a significant utility as new therapeutics and biomarkers. In this study, the levels of 2,083 microRNAs (miRs) in fifteen CSF samples from ten infants with IVH were measured using miRNA whole transcriptome sequencing. 587 miRs were differentially expressed in the CSF extracted at least two months after injury, compared to CSF extracted within the first month of injury. Gene ontology (GO) uncovered key pathways targeted by differentially expressed miRs including the MAPK cascade and the JAK/STAT pathway. Astrogliosis is known to occur in preterm infants, and we hypothesised that this could be due to abnormal CSF-miR signalling resulting in dysregulation of the JAK/STAT pathway -a key controller of astrocyte differentiation. We then confirmed that treatment with IVH-CSF promotes astrocyte differentiation from human foetal neural progenitor cells (NPCs) and that this effect could be prevented by JAK/STAT inhibition. Taken together, our results provide novel insights into the CSF-NPCs crosstalk following perinatal brain injury and reveal novel targets to improve neurodevelopmental outcomes in preterm infants.